КРИТЕРІЇ ОЦІНЮВАННЯ ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ МАЙБУТНЬОГО КЕРІВНИКА ТАНЦЮВАЛЬНОГО КОЛЕКТИВУ (Педагогіка вищої та середньої школи, 2009)
This article discusses the problems of diagnosing students' knowledge. Criteria for assessing knowledge, described the stages of the experiment, derived percentages of knowledge of students before and after the experiment.